Faktor Risiko Unsafety Action dan Unsafety Condition yang Berhubungan dengan Kecelakaan Kerja pada Pekerja Bongkar Muat Batu Bara di Pelabuhan Laut Meulaboh - Desi Maulina; Maiza Duana; Onetusfifsi Putra; Jun Musnadi Is; Dian Fera (Jurnal Kesehatan Amanah, 2025)
The initial survey conducted by researchers at the Port of Meulaboh observed the working processes of the PBM (Port Operators) of the Coal Company. Based on field data, there were 3 cases due to unsafe actions such as being struck by lifting equipment, falling, and being trapped, and there was 1 case due to an unsafe condition where the work accident occurred due to slipping. The research aims to identify risk factors of unsafe actions and unsafe conditions related to work accidents among coal unloading workers at Meulaboh Sea Port. Quantitative analytical study using a cross-sectional design is the methodology employed. Thirty unloading workers make up the study's population and sample size (total sampling). Both univariate and bivariate data analysis are employed. The findings indicated a strong correlation between dangerous condition factors (P value = 0.017 and PR = 2.5) as well as risky behavior characteristics (PR = 4.250 and P value = 0.002). and workplace mishaps involving employees.